United States : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2010)
This Selected Issues Paper of the United States analyses the Report on Standards and Codes (ROSC) and the Detailed Assessment Report (DAR) on the current state of the U.S. implementation of the Basel Core Principles for Effective Banking Supervision. The assessment identifies key weaknesses in the regulatory and supervisory framework, and mentions recommendations to improve the compliance measures. The report also summarizes assessment of the U.S. securities and futures market regulatory system. Greater focus on systemic issues relating to both securities and futures markets are recommended to make the overall regulatory system more robust.